Fluid Overload Management in HELLP Syndrome with Pulmonary Edema Underwent Caesarean Section - Agustina, Mona; Christopher Ryalino (HM Publisher, 2023)
Introduction: HELLP (hemolysis, elevated liver enzymes, and low platelets) syndrome is a multisystemic disorder. HELLP syndrome is a life-threatening condition with high maternal and infant mortality rates. This study aimed to present an unexpected case of HELLP syndrome complicated by pulmonary edema. Case presentation: A 40-year-old woman, 80 kg, who was 26-27 weeks into her pregnancy, came to the obstetric department due to fever and nausea in the past three days. She was then referred to the internal medicine department and diagnosed with dengue fever by the symptom of fever and thrombocytopenia. After two days of in-patient treatment, the obstetrician diagnosed her with HELLP syndrome, followed by elevated liver enzymes. She was then posted for an urgent caesarean section, and we managed this case under general anaesthesia. Postoperatively, we aimed for -500 to -1,000 mL cumulative fluid balance to avoid further hypovolemia. Conclusion: The patient showed improvement, as evidenced by chest X-ray and oxygen saturation. Management of fluid overload in this patient with HELLP syndrome was challenging. On the second day in ICU, the antibiotic was changed from meropenem combined with levofloxacin to meropenem combined with amikacin because the leucocyte level increased and procalcitonin level increased in 48-72 hours.